Effect of Multisession Progressive Gait-Slip Training on Fall-Resisting Skills of People with Chronic Stroke: Examining Motor Adaptation in Reactive Stability - Shamali Dusane; Tanvi Bhatt (Brain Sciences, 2021)
Background: This study examined whether a multisession gait-slip training could enhance reactive balance control and fall-resisting skills of people with chronic stroke (PwCS). Methods: A total of 11 PwCS underwent a four-week treadmill-based gait-slip training (four sessions). Pre- and post-training assessment was performed on six intensities of gait-slips (levels 1–6). Training consisted of 10 blocks of each progressively increasing intensity (four trials per block) until participants fell at >2 trials per block (fall threshold). In the next session, training began at a sub-fall threshold and progressed further. Fall outcome and threshold, number of compensatory steps, multiple stepping threshold, progression to higher intensities, pre- and post-slip center of mass (CoM), state stability, clinical measures, and treadmill walking speed were analyzed. Results: Post-training, PwCS demonstrated a reduction in falls and compensatory steps on levels 5 and 6 (p < 0.05) compared to pre-training. While an increase in pre-slip stability was limited to level 6 (p < 0.05), improvement in post-slip stability at lift-off was noted on levels 2, 3, and 5 (p < 0.05) along with improved post-slip minimum stability on levels 5 and 6 (p < 0.05). Post-training demonstrated improved fall (p < 0.05) and multiple stepping thresholds (p = 0.05). While most participants could progress to level 4 between the first and last training sessions, more participants progressed to level 6 (p < 0.05). Participants’ treadmill walking speed increased (p < 0.05); however, clinical measures remained unchanged (p > 0.05). Conclusions: Multisession, progressively increasing intensity of treadmill-based gait-slip training appears to induce significant adaptive improvement in falls, compensatory stepping, and postural stability among PwCS.